Let's go to a construction site - Amos, Janine; Reed, Neil. (New York : M. Cavendish, 1990)
Describes how a building is constructed, from the surveying of the land to the inspection of the finished structure.
Half title: Construction site.
Includes index.
8 13 20 29
Keywords: House construction; House construction -- Juvenile literature